The antibiotics roseoflavin and 8-demethyl-8-amino-riboflavin from Streptomyces davawensis are metabolized by human flavokinase and human FAD synthetase - Pedrolli, Danielle B.; Nakanishi, Shinobu; Barile, Maria; Mansurova, Madina; Carmona, Eleonora C. [UNESP]; Lux, Andreas; Gaertner, Wolfgang; Mack, Matthias (Pergamon-Elsevier B.V. Ltd, 2011)
The non-pathogenic Gram-positive soil bacterium Streptomyces davawensis synthesizes the riboflavin (vitamin B(2)) analogs roseoflavin (RoF) and 8-demethyl-8-amino-riboflavin (AF). Both compounds are antibiotics. Notably, a number of other riboflavin analogs are currently under investigation with regard to the development of novel antiinfectives. As a first step towards understanding the metabolism of riboflavin analogs in humans, the key enzymes flavokinase (EC 2.7.1.26) and FAD synthetase (EC 2.7.7.2) were studied. Human flavokinase efficiently converted RoF and AF to roseoflavin mononucleotide (RoFMN) and 8-demethyl-8-amino-riboflavin mononucleotide (AFMN), respectively. Human FAD synthetase accepted RoFMN but not AFMN as a substrate. Consequently, roseoflavin adenine dinucleotide (RoFAD) was synthesized by the latter enzyme but not 8-demethyl-8-amino-riboflavin adenine dinucleotide (AFAD). The cofactor analogs RoFMN, AFMN and RoFAD have different physicochemical properties as compared to FMN and FAD. Thus, the cofactor analogs have the potential to render flavoenzymes inactive, which may negatively affect human metabolism. RoF, but not AF, was found to inhibit human flavokinase. In summary, we suggest that AF has a lower toxic potential and may be better suited as a lead structure to develop antimicrobial compounds. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Antibiotics; Flavin analogs; Human flavokinase; Human FAD synthetase; Streptomyces davawensis